PTU-035 The BSG position statement on sessile serrated lesions will have limited impact on surveillance workload. (8th June 2018) - Coleman, Helen; Shah, Rajeev; O'Neill, Ciaran; Cameron, Iain; Owen, Tracy; Dickey, William; Loughrey, Maurice
Abstract : Introduction: There is a lack of evidence to inform guidelines for the management of pre-malignant colorectal sessile serrated lesions (SSL). Northern Ireland (NI) is the only UK region where pathologists have diagnosed SSL (or synonyms) during reporting of Bowel Cancer Screening (BCS) specimens since inception of the programme. The aim of this study is to profile SSL diagnoses, and their risk stratification for surveillance, within BCS in NI. Methods: The NI BCS programme was initiated in April 2010, targeting 60–74 year olds through faecal occult blood testing (FOBt). Characteristics of SSL diagnoses were evaluated within the enhanced pathology database completed by all histopathologists reporting BCS specimens in NI. Data up to end March 2017 were considered for analysis, incorporating data on over 17 000 histopathological BCS specimens reviewed at one of four pathology laboratories. Individuals who received a colorectal cancer diagnosis were excluded from analysis. Results: SSL were reported in 337 individuals, representing 6.7% of all 5041 individuals who had a non-malignant histopathological BCS specimen reviewed. One male met criteria for serrated polyposis syndrome, and was excluded from further analysis. Of the remaining 336 SSL cases, 208 (61.9%) were male and 81% had only right-sided SSL detected. Large (≥10 mm) SSL or SSL with dysplasia accounted for 82 cases (24.4%), of which only 22 (6.5% of SSL and 0.4% of total 5041 individuals) did not have concurrent conventional adenomas that would already warrant more frequent surveillance. Conclusions: SSL cases within this FOBt screening population were predominantly male and right-sided. Of all cases of large or dysplastic SSL, 93.5% also had high or intermediate risk adenomas, which would already require follow-up colonoscopy surveillance at one or three years according to adenoma surveillance guidelines. Therefore, the 2017 British Society of Gastroenterology position statement on serrated polyps will have limited impact in this clinical setting. The clinical significance of concurrent adenomas and SSLs remains to be established.